The safety and efficacy of dabrafenib plus trametinib for patients with brain metastatic melanoma: a systematic review and meta-analysis - Mohammad Amin Habibi; Mohammad Sina Mirjani; Bardia Hajikarimloo; Mohsen Dashti; Afsaneh Ghasemzadeh; Seyed Hesam Hojjat; Mohammad Shahir Eftekhar; Kosar Doraghi; Yalda Ghazizadeh; Fateme Aghaei; Shaghayegh Karami; Mehrshad Edalat; et al. (Discover Oncology)
Abstract Background Brain metastases (BM) are common complications of metastatic cancer and typically occur in patients with melanoma. This study aims to investigate the dabrafenib plus trametinib for patients diagnosed with melanoma brain metastasis (MBM). Method This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed, Embase, Scopus, and Web of Science were searched until January 1, 2025. Data on the neurological progression-free survival (PFS), overall survival (OS), radiological response rate, whether intracranial and total, and adverse events were collected. Quality assessment of the studies was conducted using the Newcastle–Ottawa Scale (NOS). The STATA version 17.0. has been used for analysis of the outcomes. Results Eleven studies met the inclusion criteria. Our results showed pooled 6-month OS rate of 76% (95% CI [69–84%]), 1-year OS of 45% (95% CI [38–51%]), 6-month PFS rate of 46% (95% CI [40–52%]), 1-year PFS of 22% (95% CI [13–30%]), disease control rate (DCR) of 71% (95% CI [61–80%]), overall response rate (ORR) of 45% (95% CI [33–57%]), complete response rate (CRR) of 4% (95% CI [0–11%]), partial response rate (PRR) of 47% (95% CI [31–63%]), progressive disease rate (PDR) of 29% (95% CI [13–44%]), and stable disease rate (SDR) of 21% (95% CI [14–27%]). The pooled intracranial CRR, intracranial PRR, intracranial SDR, and intracranial PDR were 4% [95% CI: 1–8%], 42% [95% CI: 32–53%], 24% [95% CI: 18–31%], and 24% [95% CI: 13–34%], respectively. Conclusion These findings underscore the effectiveness of dabrafenib plus trametinib in managing MBM, offering potential benefits in disease control and patient outcomes.